Enteroglucagon and experimental intestinal carcinogenesis in the rat. Issue 1 (January 1987) - Savage, A P; Matthews, J L; Ghatei, M A; Cooke, T; Bloom, S R
Abstract : To assess the association between the putative intestinal trophic hormone enteroglucagon and the development of intestinal tumours, four groups of 20 rats underwent either jejunal transection or 20%, 50%, or 80% proximal small bowel resection. Tumours were induced with azoxymethane 10 mg/kg weekly for 12 weeks. At 26 weeks there was a promotion of colonic neoplasia from a median of 0.5 (range 0-3) per rat in the transection group to 1.0 (0-3) in the 50% resected group (p less than 0.01) but no significant promotion in the 80% resection group. In the small bowel, increasing resection resulted in a progressive promotion of tumours from a median of 1.0 (range 0-3) per rat in the transection group to 2.0 (0-5) in the 50% resection group (p less than 0.001) and 3.0 (0-11) in the 80% group (p less than 0.01). Plasma enteroglucagon was measured at 2, 16, and 26 weeks and was raised seven-fold in the 80% resected group (p less than 0.001). There was a significant correlation between enteroglucagon concentrations and number of duodenal tumours but not colonic tumours. Crypt cell production rate in the duodenum increased from 11.5 +/- 1.9 to 29.2 +/- 1.4 cells/crypt/h in the 80% resected group (p less than 0.001) and showed a close correlation with both enteroglucagon levels and tumour promotion in the small bowel. There were no changes in crypt cell production rate in the colon with resection. This study shows a close association between enteroglucagon concentrations, promotion of tumours and crypt cell production rate in the duodenum but not in the colon.